2012
DOI: 10.1111/j.1365-2591.2012.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin‐C promotes differentiation of rat dental pulp cells in vitro

Abstract: TN-C promoted differentiation of rat dental pulp cells by the activation of Notch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…), actively participates in physiological mineralization (Mackie & Murphy ) and promotes the differentiation of rat dental pulp cells (Matsuoka et al . ). In the present study, TNC was found to be significantly elevated under SMG conditions, which indicates that SMG might also function as a promoter of the odontogenic differentiation of hDPSCs through a TNC‐mediated mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…), actively participates in physiological mineralization (Mackie & Murphy ) and promotes the differentiation of rat dental pulp cells (Matsuoka et al . ). In the present study, TNC was found to be significantly elevated under SMG conditions, which indicates that SMG might also function as a promoter of the odontogenic differentiation of hDPSCs through a TNC‐mediated mechanism.…”
Section: Discussionmentioning
confidence: 97%
“…Common extracellular matrix molecules were selected for immunohistochemical analysis (1719). Five-micrometer paraffin embedded sections were dewaxed, and treated with 3% hydrogen peroxide after antigen retrieval.…”
Section: Methodsmentioning
confidence: 99%
“…Primer sequence and size used in this study were shown in Table 2 . Quantification was performed by comparing the levels obtained with standard samples as a previous study [ 21 ]. In the present study, the concentrations of cDNA in the unstimulated samples were 0.2, 0.5, 1.0 and 2.0 μl.…”
Section: Methodsmentioning
confidence: 99%